Tinjauan Hukum Bagi Penolak Vaksinasi Di Masa Pandemic Covid-19 Terhadap Sanksi Pidana - Miharja, Marjan; Mustajab, Wahyu; Akbar, Sultan; Setiawan, Heri (Fundamental: Jurnal Ilmiah Hukum, 2022)
Spread of Covid-19, One of them is to carry out mass vaccinations that are given to the public free of charge. But not a few who refuse to be vaccinated for one reason or another, because of the incitement of others and theories stating that vaccines are dangerous and so on. So everyone who has been designated as the target recipient of the Covid-19 Vaccine but refuses it can be subject to administrative sanctions in accordance with Article 13A of Presidential Regulation Number 14/2021. In addition, vaccine refusals can be subject to criminal sanctions because they are considered to have hindered the handling of Covid-19. The research method used is juridical-normative with a statutory approach, namely Presidential Regulation no. 14 of 2021 concerning Amendments to Presidential Regulation No. 99 of 2020 concerning the Procurement of Vaccines and the Implementation of Vaccinations in the Context of Combating the Covid-19 Pandemic. Another approach used is a conceptual approach by studying the principles, principles, and doctrines of legal science that are used as guidelines to answer and provide legal arguments on related legal issues.